Put (-2) where x is, then evaluate.

3(-2) + 2 - (4(-2) + 5)

= -6 + 2 - (-8 + 5)

= -6 + 2 -(-3)

= -6 + 2 + 3

= -4 + 3

3(-2) + 2 - (4(-2) + 5)

= -6 + 2 - (-8 + 5)

= -6 + 2 -(-3)

= -6 + 2 + 3

= -4 + 3

**= -1**3(-2) + 2 - (4(-2) + 5)

= -6 + 2 - (-8 + 5)

= -6 + 2 -(-3)

= -6 + 2 + 3

= -4 + 3

The equation is: 3x +2 -{4x+ 5}

grouping the similar variables together, we have

3x +2 - 4x - 5

applying the value of x

=3(-2) + 2 -4(-2) -5

=-6 + 2 + 8 -5

=-1

hence value of equation is -1

grouping the similar variables together, we have

3x +2 - 4x - 5

applying the value of x

=3(-2) + 2 -4(-2) -5

=-6 + 2 + 8 -5

=-1

hence value of equation is -1

Didn't find the answer you were looking for?